KEPUASAN KERJA GURU BERDASARKAN STATUS KEPEGAWAIAN DAN JENIS KELAMIN - Roby Maiva Putra; Raja Arlizon (TANJAK, 2021)
The education process will run optimally if teachers as educators have high interest and satisfaction with their profession. This study aims to: (1) see the description of teacher job satisfaction, (2) see differences in teacher job satisfaction based on civil servant and non-PNS status, and (3) see differences in teacher job satisfaction based on gender. This research uses descriptive quantitative method. This research was conducted at State Vocational High Schools throughout Kuantan Singingi Regency, Riau Province. The population in this study were teachers registered in the 2017/2018 school year. Samples were taken using proportional random sampling technique and obtained as many as 206 people, consisting of 85 men and 121 women or 110 people with civil servant status and 96 with non-PNS status. Data analysis was performed using a percentage formula and simple regression. The findings of this study are: (1) most of the teachers' job satisfaction is in the high category with a percentage of 83.49%, (2) there is a significant difference between the job satisfaction of teachers who are PNS and Non-PNS. The job satisfaction of teachers with PNS status is higher than teachers with non PNS status, (3) there is a significant difference between the job satisfaction of male and female teachers. The job satisfaction of female teachers is higher than that of male teachers. The results of this study can be used as input for the Education Office and school principals in order to increase the number of programs that can increase teacher job satisfaction.